2022
DOI: 10.1108/ijmf-06-2021-0278
|View full text |Cite
|
Sign up to set email alerts
|

Bank stock valuation theories: do they explain prices based on theories?

Abstract: PurposeThe objective of this paper is to investigate the validity of stock valuation theories and their forecasting ability by conducting an empirical study. It employs four most commonly used theories which are then tested using 19-year banking-firm market data. The usefulness of these models demonstrates with promising results.Design/methodology/approachThis paper conducts a multi-country study using the multi-model testing approach to evaluate validity of theories and forecast accuracy of banking firms. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Nevertheless, among the various approaches to measuring bank valuation, research (Leong et al 2022) concluded that the valuation uses an approach Price to Earning (P/E) has the highest predictive ability compared to approaches Residual Income Model (RIM), Dividend…”
Section: Determinants Of Banking Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, among the various approaches to measuring bank valuation, research (Leong et al 2022) concluded that the valuation uses an approach Price to Earning (P/E) has the highest predictive ability compared to approaches Residual Income Model (RIM), Dividend…”
Section: Determinants Of Banking Valuationmentioning
confidence: 99%
“…Company value is determined by various factors, both internal and external (Tobin and Brainard 1976). With various approaches to measuring company value, the determinants of 12 valuation are also varied, including the business environment (macro) and company-specific (micro) (Leong et al 2022).…”
Section: Determinants Of Banking Valuationmentioning
confidence: 99%